Understanding the impact of different post-digestion enzymatic inhibition methods and storage conditions on standardized gastrointestinal model (INFOGEST): A case study of Pleurotus ostreatus mushroom biomass - Araújo-Rodrigues, Helena; Salsinha, Ana Sofia; Coscueta, Ezequiel R.; Relvas, João Bettencourt; Tavaria, Freni K.; Pintado, Manuela E. (Food research international, 2025)
INFOGEST became the standard digestion protocol to address inconsistencies in gastrointestinal tract (GIT) digestion protocols. However, sample collection, enzymatic inactivation methods, and storage conditions can significantly impact the accurate assessment of food compounds. This study investigates for the first time the impact of inactivation methods (thermal, pH-based, and specific inhibitors) and storage conditions (freezing and freeze-drying), following INFOGEST protocol on macronutrients of Pleurotus ostreatus biomass (used as a model food matrix). The results revealed that groups of macromolecules are differently affected by inactivation and storage methods. For α-glucans and glucans with different linkages than (1 → 3)(1 → 6)-β-glucans, enzyme inactivation seemed to prevent overestimation of enzymatic activity, with freezing emerging as the most promising storage method. For this carbohydrate group, no significant differences were found between inactivation strategies. The results suggested that freezing and thermal inactivation preserve peptide solubility. Additionally, freeze-drying may promote phenolic degradation and reduce antioxidant potential. Depending on the GIT phase, pH-based and specific inhibitors negatively impact these variables. The storage seemed to have no significant effect on fatty acids, enabling the selection of storage conditions based on the stability requirements of other macronutrient groups. Overall, thermal inactivation combined with freezing emerged as an effective, low-cost, and straightforward approach, minimizing post-digestion enzymatic activity and protecting food compounds from degradation. These findings enhance the reproducibility of digestion studies, facilitating inter-laboratory comparisons. Future studies should explore additional macronutrient-rich matrices, particularly those with diverse protein and lipid profiles, to expand the applicability of these findings. [Display omitted] •Freezing preserves glucan fraction without differences among inactivation methods.•Freezing and thermal inactivation preserve peptide solubility and integrity.•Freeze-drying promotes phenolic degradation and reduces antioxidant activity.•No significant effect of fatty acids storage, without key findings on inactivation.•Thermal enzyme inactivation and freezing are recommended after INFOGEST digestion.